Dandy-Walker Syndrome Associated with Scoliosis: Clinical Presentation, Preoperative Assessment, and Treatment - Athanasios I. Tsirikos; Sarah J. Wordie (Case Reports in Orthopedics)
Dandy-Walker syndrome (DWS) affects the posterior cranial fossa resulting in characteristic dysmorphic facial and body features. Scoliosis is not typically reported as an extracranial manifestation of this condition. We present a 12-year-old female patient who developed a right thoracic scoliosis measuring 60° with increased lumbar lordosis. Scoliosis correction was indicated to alleviate back pain, improve cosmesis, and prevent respiratory complications. A multidisciplinary preoperative assessment included cardiac, respiratory, anaesthetic, and neurology reviews. She underwent a posterior spinal fusion from T2 to L3 with pedicle hook/screw and rod instrumentation and a combination of locally harvested autologous and allograft bone. This resulted in excellent deformity correction and a balanced spine in the coronal and sagittal planes. The patient made an uneventful recovery and returned gradually to her normal level of activities. She was monitored in clinic until she completed her growth (4 years after surgery); the satisfactory surgical outcome was maintained at follow-up and was associated with high patient satisfaction. Scoliosis can occur in children with DWS with resemblance to adolescent idiopathic scoliosis in regard to type of coronal deformity, age at presentation, surgical techniques, and postoperative recovery. Early identification of scoliosis in patients with DWS can allow preoperative planning and prompt surgical management in order to reduce the risk of significant morbidity which can occur if the scoliosis is allowed to deteriorate. Excellent deformity correction can be achieved and maintained beyond skeletal maturity in order to improve physical appearance, as well as preserve level of function and quality of life.